Cloning and expression of an NADP(+)-dependent alcohol dehydrogenase gene of Entamoeba histolytica. - Kumar, A (1992)
Ethanol is the major metabolic product of glucose fermentation by the protozoan parasite Entamoeba histolytica under the anaerobic conditions found in the lumen of the colon. Here an internal peptide sequence determined from a major 39-kDa amoeba protein isolated by isoelectric focusing followed by SDS/PAGE was used to clone the gene for the E. histolytica NADP(+)-dependent alcohol dehydrogenase (EhADH1; EC 1.1.1.2). The EhADH1 clone had an open reading frame that was 360 amino acids long and encoded a protein of approximately 39 kDa (calculated size). EhADH1 showed a 62% amino acid identity with the tetrameric NADP(+)-dependent alcohol dehydrogenase of Thermoanaerobium brockii. In contrast, EhADH1 showed a 15% amino acid identity with the closest human alcohol dehydrogenase. EhADH1 contained 18 of the 22 amino acids conserved in other alcohol dehydrogenases, including glycines involved in binding NAD(P)+ as well as histidine and cysteine residues involved in binding the catalytic zinc ion. Like the T. brockii alcohol dehydrogenase, EhADH1 lacked a 23-amino acid stretch present in other alcohol dehydrogenases that includes four cysteines that bind a second noncatalytic zinc ion. An EhADH1-glutathione-S-transferase fusion protein showed the expected NADP(+)-dependent alcohol dehydrogenase and NADPH-dependent acetaldehyde reductase activities. The enzymatic activities of the EhADH1 fusion protein were inhibited by pyrazole and 4-methylpyrazole.